2020
DOI: 10.3389/fpls.2020.01106
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated High Affinity Copper Transport Alters Iron Homeostasis in Arabidopsis

Abstract: The present work describes the effects on iron homeostasis when copper transport was deregulated in Arabidopsis thaliana by overexpressing high affinity copper transporters COPT1 and COPT3 ( COPT OE ). A genome-wide analysis conducted on COPT1 OE plants, highlighted that iron homeostasis gene expression was affected under both copper deficiency and excess. Among the altered genes were those encoding the iron up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…This difference could be due to the cross talk between Fe and Cu homeostasis ( Carrió-Seguí et al, 2019 ; Rai et al, 2021 ), such as increased activities of enzymes with a Fe cofactor (e.g., Fe superoxide dismutase) that could compensate for decreased activities of functionally analogous enzymes that require a Cu cofactor (e.g., Cu/Zn-superoxide dismutase; Kliebenstein et al, 1998 ; Cohu and Pilon, 2007 ). Perea-García et al (2020) observed an increase in root and shoot Fe concentrations in wild type Arabidopsis under Cu deficiency, and Waters and Armbrust (2013) found increased Cu concentrations under Fe deficiency. Additionally, it has been observed that Cu deficiency induces the expression of Cu-II chelate reductase activity in root tips ( Bernal et al, 2012 ).…”
Section: Discussionmentioning
confidence: 96%
“…This difference could be due to the cross talk between Fe and Cu homeostasis ( Carrió-Seguí et al, 2019 ; Rai et al, 2021 ), such as increased activities of enzymes with a Fe cofactor (e.g., Fe superoxide dismutase) that could compensate for decreased activities of functionally analogous enzymes that require a Cu cofactor (e.g., Cu/Zn-superoxide dismutase; Kliebenstein et al, 1998 ; Cohu and Pilon, 2007 ). Perea-García et al (2020) observed an increase in root and shoot Fe concentrations in wild type Arabidopsis under Cu deficiency, and Waters and Armbrust (2013) found increased Cu concentrations under Fe deficiency. Additionally, it has been observed that Cu deficiency induces the expression of Cu-II chelate reductase activity in root tips ( Bernal et al, 2012 ).…”
Section: Discussionmentioning
confidence: 96%
“…SPL7 does not only govern Cu homeostasis signaling pathway but also represses Fe-homeostasis genes, IRON MANs (IMAs) and bHLH Ib, by an unknown strategy (Kastoori Ramamurthy et al, 2018). A recent report found that excessive Cu reduces the expression of FIT but activates bHLH Ib in the COPT1 overexpression plants (Perea-García et al, 2020). Thus, further investigation in depth is required to uncover the molecular mechanism underling the crosstalk between Fe and Cu homeostasis.…”
Section: Crosstalk Between Cu and Fe Homeostasis Signaling Networkmentioning
confidence: 99%
“…COPT2 is also up‐regulated by Fe or (and) Cu deficiency (Perea‐García et al, 2013). In addition, several studies reported the crosstalk between Fe and Cu signalling networks in plants (Bernal et al, 2012; Garcia‐Molina, Marino, Lehmann, & Leister, 2020; Kastoori Ramamurthy et al, 2018; Perea‐García et al, 2013, 2020; Puig et al, 2007; Waters et al, 2012; Waters & Armbrust, 2013). However, the molecular mechanism underling Fe and Cu crosstalk remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…These plants show an altered expression of several Fe homeostasis genes, including genes of the Fe uptake system and their transcriptional regulators. This suggests the relevance of a correct interconnection between Cu and Fe homeostasis under metal deficiency growth conditions (Perea-García et al, 2020).…”
Section: Introductionmentioning
confidence: 92%